2016
DOI: 10.1016/j.clinbiomech.2015.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of muscle synergies and activation–deactivation patterns in subjects with anterior cruciate ligament deficiency during walking

Abstract: Background: The knowledge of muscle activation patterns when doing a certain task in subjects with anterior cruciate ligament deficiency could help to improve their rehabilitation treatment. The goal of this study is to identify differences in such patterns between anterior cruciate ligament-deficient and healthy subjects during walking.Methods: Electromyographic data for eight muscles were measured in a sample of eighteen subjects with anterior cruciate ligament deficiency, in both injured (Ipsilateral group)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 25 publications
(43 reference statements)
3
23
0
Order By: Relevance
“…The number of synergies were similar in healthy and amputee groups which suggested that the complexity of muscle synergy are analogous due to similar control strategy used in the central nervous system (CNS). This study supports the findings of the [8] which analysed subjects with ACL deficiency. The VAF c analysis showed a higher VAF c using 5 synergies however, 4 synergies were believed to provide more distinct synergy groups of muscle EMG contents.…”
Section: D)supporting
confidence: 81%
See 2 more Smart Citations
“…The number of synergies were similar in healthy and amputee groups which suggested that the complexity of muscle synergy are analogous due to similar control strategy used in the central nervous system (CNS). This study supports the findings of the [8] which analysed subjects with ACL deficiency. The VAF c analysis showed a higher VAF c using 5 synergies however, 4 synergies were believed to provide more distinct synergy groups of muscle EMG contents.…”
Section: D)supporting
confidence: 81%
“…In all the studies associated with walking, a very insignificant change has been shown in the activation profiles however, a considerable difference has been illustrated in the muscle weightings. Other groups applied the NNMF technique to investigate the difference between healthy and pathological populations [6,8]. Clark et al [6] reported, in post-stroke subjects, similar activation profiles with fewer synergies were required to have a high VAF during walking when compared to healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an insignificant change was observed in activation profiles. Several studies implemented NNMF for comparison of healthy and pathological populations [4,5,7,8]. Clark et al [7] reported, lower number of synergy groups were required to achieve a high VAF in post-stroke patients compared to the healthy population.…”
Section: Introductionmentioning
confidence: 99%
“…Clark et al [7] reported, lower number of synergy groups were required to achieve a high VAF in post-stroke patients compared to the healthy population. Serrancoli et al [8] found, anterior cruciate ligament (ACL) deficiency would cause a slight change in activation profiles of ACL patients compared to HS. In our previous works [4,5], we investigated the difference in muscle synergy components between healthy and elderly TA subjects during ramp ascending and descending.…”
Section: Introductionmentioning
confidence: 99%